Reasons for Cancellation of Elective Surgical Operations: A Cross-sectional Study from a Tertiary Care Centre in North-East India - LALTANPUII SAILO (JCDR Research and Publications Private Limited, 2021)
Introduction: Cancellation of elective surgical operations is defined as an elective operation which is not performed on the scheduled date. The rates and the reasons for cancellation vary in different parts of the world. Cancellation causes increased cost of treatment, loss of daily wage and mental trauma. It also causes under utilisation of hospital resources and loss of training opportunities to surgical trainees. Aim: To estimate the rate of cancellation of elective surgical operations in a tertiary care centre in North-East India and determine the reasons for cancellation. Materials and Methods: A prospective cross-sectional study was conducted at a 500 bedded, North-Eastern Indira Gandhi Regional Institute of Health and Medical Sciences, Shillong, Meghalaya, India, from January 2018 to September 2018. All consecutive elective surgical cases scheduled during this period were included in the study. The rate and the reasons for cancellation were noted. Descriptive statistics was used for analysis of the results. Results: Out of 1812 elective surgical operations scheduled during the study period, 491 operations (27.10%) were cancelled. The most common reasons for cancellation were shortage of time (78.62%), medical causes (10.79%) and administrative problems (4.48%). Cancellation rate was highest in the Department of Surgical Oncology (40.23%), followed by Departments of Orthopaedics (34.51%) and Obstetrics and Gynaecology (OG) (31.02%). Conclusion: The rate of cancellation of elective surgical operation was high (27.10%) and the most common reason was shortage of time and Surgical Oncology Department had highest rate of cancellation.